Pengembangan Soal Hots Subtema Bekerja Sama Mencapai Tujuan Di Kelas VI SDN 25 Pontianak Utara - Satya Nugraha; Kartono Kartono; Asmayani Salimi (Departement of Mathematics Education, 2024)
The overall goal of this research is to create and provide a set of questions based on High Order Thinking Skills (HOTS). The purpose of this study's description questions is to create HOTS assessments or test questions for grade VI students at SDN 25 North Pontianak that focus on the subtheme of cooperating to achieve goals. This kind of study employs the Borg & Gall model for research and development (R&D), with the development stages restricted to the seventh step: (a) information gathering and research; (b) planning; (c) developing the primary form of the product; (d) preliminary field; (e) main product revision; (f) main field testing; and (g) operational product revision. The approach taken in this research is a mixed method approach (mixed method). The subjects of this study were 28 students from class VI B SDN 25 North Pontianak in the 2023/2024 school year. This study used instruments in the form of interviews, questionnaires and written tests. The study's findings were as follows: The target was attained by the HOTS question products on the cooperation subtheme, with an average of 4.7 in the very good category, according to the findings of product validation tests conducted by two experts on the material, construction, and language elements. (2) the results of the item analysis on six description items revealed that: a) all of the items are valid according to the validation analysis; b) the reliability analysis results are 0.80, including in the high reliability category; c) the results of the differentiating power analysis indicate that 50% of the questions are in the good category and 50% are in the very good category; and d) An examination of the question's difficulty level reveals that it falls into three categories: simple (4 items), moderate (1 item), and difficult (1 item).